Pieaugušo veselības izglītības organizācija un vadība primārās veselības aprūpes māsas praksē - Upmale, Ināra (Latvijas Universitāte, 2013)
Promocijas darba mērķis ir izpētīt faktorus, kas ietekmē pieaugušo veselības izglītības darba organizāciju un vadību primārās veselības aprūpes māsas praksē, ietverot arī indivīda veselības kompetenci veidojošos faktorus, un izveidot uz pierādījumiem balstītus metodiskus ieteikumus pieaugušo veselības izglītības darba organizācijai un vadībai, kas būtu izmantojami gan māszinību studiju programmās, gan primārās veselības aprūpes līmenī strādājošo māsu tālākizglītībā. N= 827 iedzīvotāji un N=106 māsas. Izmantota faktoru analīze, korelācijas analīze, ANOVA, Kruskall-Wallis tests. Noskaidrots, ka indivīda veselības kompetenci ietekmē vairāki galvenie faktori, papildus tiem, dzimums, izglītība, ienākumi. Arī māsas darbību veselības izglītības vadībā ietekmē vairāki faktori, tajā skaitā, māsas izglītība. Pēc datu analīzes izveidotas rekomendācijas.

Currently, each choice of daily life, even if a little, is associated with health. For an individual, to be able to make such decisions in everyday life that have a positive impact on health, the health competence is needed. Its promotion is one of the tasks of health education that is being implemented in primary health care nurse practice. The aim of the thesis is to explore the factors that influence health education organization and management of primary health nursing practice, including individual health competence factor, and develop evidence-based methodological recommendations of health education regarding the organization and management, which would be used in nursing graduates, and primary health care nurses working at the level of education is the author’s aim in doctoral thesis “Health education organization and management in primary health care nurse practice”. The study involved two groups of respondents: 827 inhabitants and 106 primary health care nurses. The study had two objectives. First, find out what factors determine an individuals’ health competency and then, what factors influence primary health care nurses’ possibility to promote it. The study showed that increasing the number of nurses who have obtained higher education, nursing knowledge, skills and activities in educating people, in regards of qualitativelity, is not different from the general practitioners’ knowledge and skills, and it is as effective as the doctor’s actions, moreover, cost-efficient. The author concluded, during the analysis of scientific literature, that health education, health behavior, values and environment affect formation of an individual's health competence. They help understand how to be able to better promote the public health education. The research also showed the factors that influence health education organization and management of primary health care nurse practice in our country, also as an important independent variable here appears nurses’ education. When summarizing the results of both – the factors that influence individual’s health competence and the factors that influence nurses action in educating people – the author created a recommendation algorithm for health education organization and management of primary health care nurse practice. The total amount of the Thesis is 197 pages. It consists of an introduction, 8 chapters, the main findings and conclusions. There are 214 references of literature and other sources in Latvian, English and Russian are used.
Adult Health Education Organization and Management in Primary Health Care Nurse Practice
Keywords: Izglītības vadība; veselības izglītība; māsas prakse; veselības kompetence; Education Management; nurses practice; health education; primary health care; health competence; health literacy; health behavior